Sistema de Apoio à Tomada de Decisão na Gestão de Atendimento a Pacientes com Câncer Infanto-Juvenil - Oliveira, Renato; Nascimento Filho, Lindemberg; Oliveira, Werlesson; Bandeira, Thiago; Oliveira, Mauro; Braga, Reinaldo; Oliveira, Carina (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2017)
In Brazil, cancer is the first cause of death due to illness among children and adolescents from 1 to 19 years. The Brazilian National Cancer Institute (INCA) estimates about 12,600 new cases of childhood and juvenile cancer in 2017. Although childhood and juvenile cancer is potentially curable, it is necessary an early diagnosis and urgent treatment. In this context, this article presents a Web system that assists health professionals and managers in the decision making process in order to optimize the treatment of children and adolescents with cancer. Since 2016, the system has been used at the Peter Pan Association (APP), an association for the Fight Against Child and Adolescent Cancer, located in Fortaleza-CE. The large volume of data collected by the system is organized, analyzed and monitored to feed reports, dashboards with flags and alerts, as well as spatiotemporal maps. We show how the proposed solution can contribute to increase the cure rate and improve the quality of life of children and adolescents with cancer and their families.